Impact of COVID-19 on Kazakhstan’s economy - Kenzhin, Zh.B.; Sultanova, M.B.; Aidaralieva, A.A.; Mukina, G.S.; Eniola, A.A. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: This article aims to analyze the impact of the COVID-19 outbreak on the economy of Kazakhstan, identi-fy positive and negative factors, and propose recommendations for further economic development and overcoming the crisis based on the opinions of leading experts in the field. Methods: A theoretical review of the scientific literature on the research topic. Results: Using scientific analysis based on publications dated 2020-2021 and statistical data from official infor-mation resources, the main directions of Kazakhstan’s economic development were outlined. The analysis of the situa-tion in the sphere of economic research was carried out. Economic freedom indicator and business climate ranking were provided. Conclusions: Since assessment and prediction of the economic situation in Kazakhstan have been performed in accordance with various criteria and methods, it is therefore difficult to obtain an unambiguous picture of socio-economic threats induced by the processes taking place in the global economy nowadays. Nevertheless, the analysis of economic indicators shows that the economic well-being of the country appears to be satisfactory, and Kazakhstan has good prospects for further development in many areas. New approaches to the investment sector in the economic policy of the country are necessary to overcome the crisis caused by the pandemic. The authors propose a change in the basic approaches to regulatory policy, formulated the principles of comprehensive and effective regulation, taking into ac-count current economic challenges.
COVID-19-дың Қазақстан экономикасына әсері
Воздействие COVID–19 на экономику Казахстана
Keywords: Kazakhstan; COVID-19; economic crisis; pandemic; expert opinion; index of economic freedom; doing business rank